Hubungan Peran Orang Tua Dalam Memenuhi Kebutuhan Gizi Anak Dengan Perkembangan Anak Usia Pra Sekolah Di Tk Negeri Pembina Ampenan - Robiatul Adawiyah; Nurhayati Nurhayati; Fourlyta Hutabarat (Jurnal PRIMA, 2021)
Introduction: Preschool-aged children with unbalanced nutrition will experience several problems. Nutritional problems caused in the preschool age group. According to the 2010 Basic Health Research data in the province of West Nusa Tenggara (NTB) it was found that the malnutrition rate in preschool age children (4-6 years) based on BMI/U was 12.4 percent and malnutrition was 5.3 percent. Based on 2015 data from 105 pre-school children at Pembina Ampenan Kindergarten, 21 of them experienced less than optimal fine motor and artistic development compared to other students.Objective: The purpose of this study was to determine the relationship between the role of parents in meeting the nutritional needs of children with the development of preschool children in the Pembina State Kindergarten of Ampenan.Methods: The research design is descriptive correlation. The sampling technique was purposive sampling so that the number of samples obtained was 86 people. The instrument used was the Developmental Pre-Screening Questionnaire (KPSP). Data analysis was done by Chi-Square test.Results: The results showed that there was a relationship between the role of parents in meeting the nutritional needs of children and the development of preschool-aged children at the Pembina Ampenan State Kindergarten, this was evidenced by the p value of 0.000 with a significant level of 0.05 (p < ).Conclusion: If parents play a good role in meeting the nutritional needs of children, then the development of children will be according to their age.